Changes in Gravitaxis and Gene-Expression in an Euglena gracilis Culture over Time - Krüger, Julia; Richter, Peter; Stoltze, Julia; Prasad, Binod; Strauch, Sebastian; Krüger, Marcus; Nasir, Adeel; Lebert, Michael (Biomolecules, 2024)
Age-dependent changes in the transcription levels of 5-day-old Euglena gracilis cells, which showed positive gravitaxis, 6-day-old cells without gravitactic orientation, and older cells (9- and 11-day-old, which displayed a precise negative gravitaxis) were determined through microarray analysis. Hierarchical clustering of four independent cell cultures revealed pronounced similarities in transcription levels at the same culture age, which proves the reproducibility of the cultivation method. Employing the non-oriented cells from the 6-day-old culture as a reference, about 2779 transcripts were found to be differentially expressed. While positively gravitactic cells (5-day-old culture) showed only minor differences in gene expression compared to the 6-day reference, pronounced changes of mRNAs (mainly an increase) were found in older cells compared to the reference culture. Among others, genes coding for adenylyl cyclases, photosynthesis, and metabolic enzymes were identified to be differentially expressed. The investigated cells were grown in batch cultures, so variations in transcription levels most likely account for factors such as nutrient depletion in the medium and self-shading. Based on these findings, a particular transcript (e.g., transcript 19556) was downregulated using the RNA interference technique. Gravitaxis and phototaxis were impaired in the transformants, indicating the role of this transcript in signal transduction. Results of the experiment are discussed regarding the increasing importance of E. gracilis in biotechnology as a source of valuable products and the possible application of E. gracilis in life-support systems.
CRIS-Team Scopus Importer:2024-04-05
Keywords: culture age; Euglena gracilis; gravitaxis; microarray analysis; phototaxis